To whom and why should I connect? Co-author recommendation based on powerful and similar peers. (1st August 2012) - Sie, Rory L.L.; Drachsler, Hendrik; Bitter-Rijpkema, Marlies; Sloep, Peter
The present paper offers preliminary outcomes of a user study that investigated the acceptance of a recommender system that suggests future co-authors for scientific article writing. The recommendation approach is twofold: network information (betweenness centrality) and author (keyword) similarity are used to compute the utility of peers in a network of co-authors. Two sets of recommendations were provided to the participants: Set one focused on all candidate authors, including co-authors of a target user to strengthen current bonds and strive for acceptance of a certain research topic. Set two focused on solely new co-authors of a target user to foster creativity, excluding current co-authors. A small-scale evaluation suggests that the utilitybased recommendation approach is promising, but to maximise outcome, we need to (a) compensate for researchers' interests that change over time and (b) account for multi-person co-authored papers.